STRATEGY ANALYSIS IN ACEH ISLAMIC BANK - Rico Syahputra; Yeni Absah; Beby Karina Fawzeea Sembiring (CV. Radja Publika, 2022)
Islamic banks are the result of the Aceh Qanun policy on Islamic Financial Institutions in implementing the principles of Islamic law. Qanuns are laws and regulations similar to regional regulations that regulate the administration of the Aceh government, as well as community life in deciding regulations through DPRA meetings, so as to produce policies to be implemented. The purpose of this research is to find out and analyze strategies for increasing customer loyalty in Islamic banking in Aceh Province. Customer Relationship Management, Service Quality and Perceived Value play an important role in providing services, customer desires and understanding customer behavior in improving service quality to create Islamic Bank Customer Loyalty. This research examines 200 customers who save at Islamic banks in 5 districts/cities in Aceh. selected by purposive sampling technique, and tested using the PLS SEM statistical analysis method. The results show that Customer Relationship Management, Perceived Value has an effect on Customer Loyalty, but Service Quality has no effect on Customer Loyalty. Customer Relationship Management and Service Quality affect Perceived Value. In addition, Perceived Value mediates the relationship between Customer Relationship Management and Service Quality towards Customer Loyalty.